Constitución de compañías y sus actos que no requieren trámite notarial según las reformas societarias - Gárate Rodríguez, Mishelle Alexandra (2025)
Notary and Registry Law and its relevance as a guarantee of veracity in legal acts. The present work is developed in view of the evident lack of control after the reform of the Companies Law, published on March 15, 2023, which allows the incorporation of companies by means of private acts without notarial supervision. This deregulation has generated problems, since many users, acting outside notarial control, have made mistakes in the incorporation of companies and then seek advice from notaries to correct these errors. The objective of the study is to analyze the economic and social effects caused by the lack of legality that existed before the reform. To this end, a mixed research methodology was employed, focusing on the collection of both quantitative and qualitative data to construct and validate the hypotheses proposed. Through numerical and argumentative analysis, we sought to test the theory. The results indicate that the elimination of prior notarial control has facilitated the creation of companies, but has simultaneously led to errors in the acts of incorporation, which puts the stability of the business sector at risk. The analysis reveals that this lack of oversight not only affects the legitimacy of companies, but also undermines market confidence. In conclusion, it is essential to address the need for a verification system to ensure the correct incorporation of companies, in order to protect the business environment and foster an environment of confidence for investors and society in general.